2005
DOI: 10.1038/sj.onc.1208804
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of microdissected pancreatic intraepithelial neoplastic lesions

Abstract: Pancreatic ductal adenocarcinoma (PDAC) carries the most dismal prognosis of all solid tumours. Both the late clinical presentation of patients, due to lack of early symptoms, as well as the rapid and aggressive course of the disease contribute to the extremely high mortality of this malignancy. Recently, a multistep progression model for PDAC integrating morphological, clinical and molecular evidence has been proposed. Putative precursor lesions, termed pancreatic intraepithelial neoplasia (PanIN), are classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
121
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 43 publications
8
121
0
2
Order By: Relevance
“…This gene lies adjacent to the AGR2 gene (7p21.1) and both genes are classified as members of the same family (AGR family) due to highly similar (approximately 70%) protein sequences. Interestingly, several gene expression analyses have shown that AGR2 is upregulated in the majority of PDACs as well as pancreatic intraepithelial neoplasia (PanIN) lesions (Crnogorac-Jurcevic et al, 2003;IacobuzioDonahue et al, 2003a;Iacobuzio-Donahue et al, 2003b;Missiaglia et al, 2004;Buchholz et al, 2005). Taken together, BCMP11 is also likely to be involved in the development of PDAC.…”
Section: Discussionmentioning
confidence: 92%
“…This gene lies adjacent to the AGR2 gene (7p21.1) and both genes are classified as members of the same family (AGR family) due to highly similar (approximately 70%) protein sequences. Interestingly, several gene expression analyses have shown that AGR2 is upregulated in the majority of PDACs as well as pancreatic intraepithelial neoplasia (PanIN) lesions (Crnogorac-Jurcevic et al, 2003;IacobuzioDonahue et al, 2003a;Iacobuzio-Donahue et al, 2003b;Missiaglia et al, 2004;Buchholz et al, 2005). Taken together, BCMP11 is also likely to be involved in the development of PDAC.…”
Section: Discussionmentioning
confidence: 92%
“…1c). In addition, in silico analyses showed that AF6 mRNA levels were expressed at low levels in PanIN-3 and PDAC compared with normal tissues in the context of the proposed multistep PDAC progression model 20,21 (Fig. 1d).…”
Section: Resultsmentioning
confidence: 99%
“…This would suggest that such cells may be compensating for high levels of RAS oncoprotein signaling by increasing MTH1 levels to enhance detoxification of an oxidative lesion that contributes to the DDR and senescence induction (Moiseeva et al, 2009;Rai et al, 2009). Indeed, analysis of the ONCOMINE data sets indicates that MTH1 levels are significantly elevated in pancreatic adenocarcinomas and in nonsmall cell lung carcinomas, two human cancer types characterized by endogenous RAS mutations (Garber et al, 2001;Buchholz et al, 2005). Taken together, these various observations indicate that the oxidative stress and senescence response elicited by the RAS oncoprotein acts in large part through oxidation of substrates within the guanine deoxynucleotide pool, and that the resulting incorporation of oxidized dNTPs explains the DDR evoked as part of the resulting oncogenic RAS-induced senescence.…”
Section: Resultsmentioning
confidence: 99%